Cover Feature: How Do Actinyls Interact with Hyperphosphorylated Yolk Protein Phosvitin? (Chem. Eur. J. 53/2019). Issue 53 (1st August 2019) - Kumar, Sumit; Creff, Gaëlle; Hennig, Christoph; Rossberg, André; Steudtner, Robin; Raff, Johannes; Vidaud, Claude; Oberhaensli, François R.; Bottein, Marie‐Yasmine Dechraoui; Den Auwer, Christophe
Abstract : A multi‐spectroscopic investigation to reveal the coordination geometry of two oxocations of the actinide family (actinyl U VI, Np V ) in speciation with phosvitin is reported. A relevant model was designed for the interaction of actinyls with phosphorylated proteins, which have an important role as an iron, calcium, and magnesium storage protein in egg yolk. More information can be found in the Full Paper by C. Den Auwer et al. on page 12332 .